Special status of the seafarer in the system of labor relations - Pidpala, Iryna (Journal of Education, Health and Sport, 2016)
The article is devoted to the study of the special status of the seafarer in the system of labor relations. The objective features of labor relations with the participation of seafarers are consecrated, which give rise to the need to establish special norms that regulate the work of crew members of sea-going ships and determine the special status of a seafarer. Today, a significant number of seafarers' labor acts are in force at the international level and inUkraine. The content of many of them is inconsistent either with each other or with the general norms of labor legislation, and often gives rise to all sorts of collisions. A number of problems arise due to the fact that the work of seafarers is regulated not only by labor legislation, but also by laws that are complex in nature (one example is the Merchant Shipping Code). The large regulatory framework creates certain difficulties in law enforcement practice, contributes to the commission of violations of the law. And the activities of seafarers are still governed by the norms of the general labor legislation, which requires changes taking into account modern realities and changes in the country and in the world. Relevant is it is necessary to regulate the activities of seafarers by special legislation.